USE OF OBJECTS OF ART IN A SYMBOLIC WAY IN THE PORTRAIT OF A LADY BY HENRY JAMES (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2017)
Charles Dickens was born on 7 February 1812 in Portsmouth, England, the second son of eight children born to Elizabeth Barrow (1789-1863) and John Dickens (1785-1851), a clerk in the Navy Pay Office. Dickens' father was a well-paid clerk, but he was often in debt due to his extreme congeniality and hospitability. In 1814, Dickens moved to London, then to Chatham where he was a student. In 1824, his father was imprisoned in Marshalsea along with the rest of his family because of debt, but twelve-year-old Charles was sent to work at a blacking factory in Hungerford Market, London, a warehouse for manufacturing, packaging and distributing "blacking" or polish for cleaning boots and shoes, which enabled him to support his family.